Legal Protection of Children Born in Serial Marriages - Heddy Permana Putra; Riza Zulfikar; Bambang Slamet (Rechtsvinding, 2026)
Serial marriage, which is a marriage that is legal according to Islamic law but is not registered in a state institution, raises serious legal problems, especially for children born from the bond. This study aims to analyze the construction of Indonesian law regarding the status and protection of children's civil rights from serial marriage, both before and after the birth of the Constitutional Court Decision Number 46/PUUVIII/2010. The research method used is normative juridical with a legislative, conceptual, and comparative approach. The results of the study show that before the ruling, children from serial marriages were categorized as children out of wedlock who only had a civil relationship with their mother and mother's family based on Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, so that their basic rights — including the rights of identity, maintenance, guardianship, and inheritance — were systematically deprived. The Constitutional Court's decision in 2010 became a turning point by opening a civil relationship between the child and his biological father as long as it can be proven through science and technology, including DNA tests. However, the implementation of legal protection still faces a number of obstacles, including the rigidity of the bureaucracy of population registration, the high cost of proving nasab, and the conflict of norms between the Constitutional Court Decision and the Compilation of Islamic Law in terms of inheritance rights. From the perspective of Islamic law, child protection rests on the principles of sharia maqashid, especially the protection of nasab (hifdz annasl), which is in line with the spirit of positive legal restorative justice. This study recommends the revision of the Marriage Law, strengthening the population registration system, providing subsidized DNA test services, and issuing Supreme Court guidelines to realize legal certainty that is in favor of the best interest of the child.